Buddhist terminology of Tsongkhapa’s Lamrim: Tibetan original and Oirat translation (to the statement of the problem) - E. U. Omakaeva; G. B. Korneev (Nomadic Civilization: Historical Research)
In all traditions of Tibetan Buddhism, there are texts of the “Lamrim” class, but the most famous texts are rightfully considered to be those written by the founder of the Tibetan Gelug Buddhist tradition, Je Tsongkhapa Lobsang Drakpa (Tib. je tsong kha pa blo bzang grags pa). The Oirats and Kalmyks have long been familiar with Tsongkhapa’s Lamrim. The history of the existence of these texts in the Oirat language goes back hundreds of years. Studies of Buddhist vocabulary, especially terminology, are untenable without a deep study of Buddhism as a whole as a multidimensional phenomenon and the Buddhist linguistic picture of the world as the intersection point of two most important sign systems — religion and the language that serves it. It is the word that acts as a means of denoting the realities of everyday religious life in the past and present, as a keeper of sacred information and a translator of Buddhist values, religious tradition and culture. The purpose of the article is to review the history of the issue, describe the Tibetan original and its Oirat translation, taking into account the Buddhist terminology used by Zaya Pandita Namkhai-Jamtso when translating Lamrim. A comparative analysis of the Tibetan and Oirat texts, taking into account the Mongolian translations, will further identify the words introduced by the translator to clarify the meaning of the stanzas, the peculiarities of the translation of the proper names of Buddhas and Buddhist teachers, as well as general concepts of Buddhist philosophy.